Pengaruh Ekuitas Merek, Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Buku Fokus Di Kec. Kota Kediri : Studi Kasus Distributor Suksesi Afi Pustaka - Dandy Ferdiansyah; Taufik Akbar; Edi Murdiyanto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine: (1) the influence of brand equity on purchasing decisions, (2) the influence of product quality on purchasing decisions, (3) the influence of price on purchasing decisions, (4) the influence of brand equity, product quality, and price on purchasing decisions . This type of research uses a quantitative approach. The sample for this research is elementary schools in Kec. The city of Kediri has 45 elementary schools. The sampling technique uses saturated sampling. The data collection technique uses a questionnaire whose validity and rehabilitation have been tested. The data analysis technique used is multiple linear regression. The research results at a significance level of 5% show that: (1) there is a positive and insignificant influence of brand equity on purchasing decisions. The t value is 3.718 with a significant value of 0.001 > 0.05. (2) there is a positive and significant influence of product quality on purchasing decisions. The t value is 10.629 with a significant value of 0.000 < 0.05. (3) there is a positive and significant influence of price on purchasing decisions. The t value is 2.114 with a significant value of 0.040 < 0.05. (4) there is a simultaneous influence of brand equity, product quality and price on purchasing decisions. The Fcount value is 167.059 with a significant value of 0.000 <0.05. Calculation of multiple linear regression analysis using the regression equation obtained with a value of Y = 4.282+0.308X1+0.884X2+0.203X3